2014
DOI: 10.1007/s13224-014-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of Post Placental Copper-T-380A Insertion with Long Placental Forceps (Kelly’s Forceps) After Normal Vaginal Delivery and Cesarean Section

Abstract: Objectives To study the efficacy safety effect on menstrual cycles, expulsion, continuation, and failure rate of post placental Copper-T-380A after vaginal and cesarean birth in a tertiary center, over the period of 1 year. Methods A total of 150 women who opted for insertion of Copper-T-380A within 10 min of expulsion of placenta whether delivered vaginally or by cesarean section were enrolled into study. Women having past history of ectopic pregnancy or any genital tract infection or hemorrhagic disorders, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…This is similar to study conducted by Gupta G et al with percentage satisfaction among users after 6 weeks-91.7%, 3 months-92.9%, and 6 months-95.6%. 8 The present study showed continuation rates of about 88.23% for PPIUCD users over a follow up period of 6 months. Celen et al also showed continuation rates of 87.6% for PPIUCD at 6 months' interval.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This is similar to study conducted by Gupta G et al with percentage satisfaction among users after 6 weeks-91.7%, 3 months-92.9%, and 6 months-95.6%. 8 The present study showed continuation rates of about 88.23% for PPIUCD users over a follow up period of 6 months. Celen et al also showed continuation rates of 87.6% for PPIUCD at 6 months' interval.…”
Section: Discussionsupporting
confidence: 60%
“…In accordance to our study, no perforations were reported in post placental IUD insertion in the studies done by Kapp et al and Gupta G et al which matches our study. 7,8 In present study, the number of women who were satisfied with the use of Cu T as a contraceptive method at 1st, 2nd and 3rd follow up visit in interval delivery and postpartum delivery were 122 (88.4 %), 126 (92.5%) and 122 (92.4%) and 133 (92.3%), 130 (92.9 %) and 130 (95.6%) respectively. This emphasizes that the mode of delivery is not affecting the satisfaction level of the women .…”
Section: Discussionmentioning
confidence: 48%
“…11 Women's satisfaction after wearing PPIUCD was 91.7% after 6 weeks, 92.9% after 3 months, and 95.6% after 6 months. 12 Nearly all women (99.6%) were satisfied with IUCD at the time of insertion and 92% were satisfied at 6 week follow-up visit. 13 Continuation rate after 1 year was 91%.…”
Section: Discussionmentioning
confidence: 89%
“…Gupta et al reported the expulsion rate was 14.3% at 6 weeks, 2.9% at 3 months, and 0% at 6 months, respectively. 5 Sharma reported the expulsion rate was 5.2% at 6 months. 21 Chhari et al reported a 12% of expulsion rate in the post-placental group compared to 0% in the cesarean group.…”
Section: Discussionmentioning
confidence: 97%
“…Abdominal pain was the a year, respectively). 5,28 Heavy menstrual bleeding was the most common reason for removal. 27 In this study, the reasons for IUD discontinuation were dyspareunia, vaginal bleeding, abdominal pain, and vaginal discharge (one patient in each complaint).…”
Section: Ppiud Effectivity Side Effects and Satisfactionmentioning
confidence: 99%